The Effect of Vegetation Community and Environment on Gyrinops versteegii Growth - Rawana Rawana; Suryo Hardiwinoto; Budiadi Budiadi; Sri Rahayu (Jurnal Manajemen Hutan Tropika, 2018)
Although Gyrinops versteegii has been domesticated by local community in Sragen Regency, the environmental factors and species which have high compatibility with G. versteegii still have not known yet. The objectives of this research were 1) to know which one of those vegetation communities that gives the best the diameter and height growth of the domesticated G. versteegii, and 2) to know the environmental factors that influenced the growth of the diameter and height of the domesticated G. versteegii. Sampling was done systematically with a plot of size 20 × 20m for trees, 10 × 10m for poles, and 5 × 5m for saplings with a total of 28 plots. SPSS Program version 22 was used for cluster, one-way anova, correlation, and multiple regression analysis. The results showed that for achieving the best G. versteegii growth, the G. versteegii should be planted under the community group which was dominated by Paraserianthes falcataria, Tectona grandis, Gliricidia sepium, and Eugenia aquea. Environmental factors affecting diameter growth of G. verteegii were organic carbon of the soil and the vegetation density. Meanwhile the environmental factors affecting the height growth of G. versteegii were temperature, light intensity, relative light intensity, organic carbon, C N ratio, P, Mg, air humidity, and clay content.